Effects of curcuma longa L. rhizomes in preventing the progression of carcinogenesis in leukaemia-lymphoma rats - Md Yusoff, Yusnaini (2013)
Blood diseases including leukaemia and lymphoma are among the top ten cancers around the world. The link of anti apoptotic gene and pro apoptotic gene expression in regulating the apoptosis machinery was extensively discussed in previous studies. Curcumin the active compound in Curcuma longa L. (C. longa L.) has been proven to act as an anti cancer by inhibit the expression of Bcl-2 (anti apoptotic gene) and trigger the expression of Bax (pro apoptotic gene) in cancer researches. However, the effects of turmeric itself on the expression of those genes have not been determined in lymphoma and leukaemia research. Therefore the study present objectives were 1) to evaluate the effects of crude C. longa L. rhizomes in Sprague Dawley rats with leukaemia-lymphoma via evaluation of Bcl-2 to Bax transcription ratios in the blood and spleen using quantitative real time reverse transcription polymerase chain reaction (qRT-PCR) assay, blood analyses, urinalysis and histopathology, and 2) to examine the reliability of using N-methyl-N-nitrosourea (MNU) in inducing leukaemia-lymphoma in Sprague Dawley rats for a duration of 20 weeks. A total of 64 rats were used in this study. Rats in group A were treated as controls which were fed with a standard pellet diet. Each rat in groups B and D received daily supplementation of crude C. longa L. rhizomes at 5000 mg/kg for 20 weeks. Rats in groups C and D were injected with MNU intraperitoneally (i.p.) with a total dose of 240 mg/kg of body weight (60 mg/kg of body weight per injection for four injections in two week) to induce leukaemia-lymphoma. Blood samples were collected at weeks 0, 10 and 20 (experiment end) for haematological and serum biochemical analyses. The presence of leukaemic cells was further examined through blood smear. For molecular analysis, blood samples at weeks 0 and 20 were run for RNA extraction and qRT-PCR assay to determine the transcription ratio of Bcl-2 and Bax. Urine samples were collected once using metabolic cages before the rats were euthanised for determination of urine protein to creatinine ratio (UPC) and creatinine clearance values. Organ samples include liver, lungs, kidneys, heart, spleen and lymph nodes were taken for histopathological analysis. Spleen of each rat was also run for qRT-PCR assay. Results of blood smear showed that 64% and 100% of rats in group C had leukaemia without lymphocytosis at week 10 and week 20, respectively. The qRT-PCR assay showed the transcription ratios of Bcl-2 to Bax of the leukaemic rats were significantly higher, 3.3 fold (10.50±1.26) in blood and 10 fold (30.0±1.16) in spleen, as compared to the control rats, which indicate that MNU apparently disturbed the apoptosis pathway. High transcription ratio of Bcl-2 to Bax in the spleen was related to the splenic lesion scoring results of rats that had splenic lymphoma. Histopathology results were evidenced for the presence of metastatic malignant lymphocytes in the heart (23%), liver (23%), lungs (31%) and kidneys (15%) which encompass approximately 30% metastatic lesions observed in the rats, and malignant lymphocytes in the spleen (86%), mesenteric lymph nodes (86%) and other lymph nodes (57%) in group C rats. Serum biochemical results of the rats revealed significant elevation in the ALP, total bilirubin and uric acid levels compared to other groups, although the values were within the normal ranges. The rats had also shown significant elevation in the UPC level and decrease in the creatinine clearance value compared to control, which consistent with lymphomainduced renal injury. Interestingly, significant reduction of Bcl-2 to Bax transcription ratios in the blood and spleen of group D was observed when compared to group C. However, the transcription levels of Bcl-2 to Bax in the blood and spleen were not correlated with the lesion scoring results in the organs. The lymphoma lesion scoring results constituted in the heart, liver, lungs, kidneys, spleen, mesenteric lymph nodes and other lymph nodes of these rats were 27%, 27%, 20%, 13%, 80%, 80% and 53%, respectively, which were not significantly different form group C. Haemogram result, however, supported results of the qRT-PCR, where significant reduction in the percentages of leukaemic rats at week 10 and week 20 (19% and 88%, respectively) in group D were observed when compared to group C (64% and 100%, respectively). The UPC ratio and creatinine clearance of group D also showed a similar trend of reduction as compared to group C. In conclusion, the administration of MNU with a total dosage of 240 mg/kg successfully induced 100% leukaemia and 86% nodal and splenic lymphoma in male Sprague Dawley rats within 20 weeks period, however less than 30% of the rats had metastatic lesions in the vital organs. Urinalysis results of the rats were in accordance to the lymphoma lesions observed in the kidneys. The transcription ratios of Bcl-2 and Bax in the blood and spleen were also significantly increased and correlated to the lesion scoring results in the organs. Meanwhile, the effectiveness of crude C. longa L. rhizomes was demonstrated by the reduction in number of leukaemic rats and transcription ratio of Bcl-2 and Bax in the blood. Low transcription ratio of Bcl-2 to Bax in the spleen and urinalysis results further elucidate the effectiveness of the herb in preventing progression of carcinogenesis via inhibiting the proliferation of lymphoma cells in the spleen and minimising renal injury induced by the lymphoma cells in the rats, respectively.